Aid conditionality and military expenditure reduction in developing countries: models of asymmetric information. - Murshed, S. Mansoob; Sen, Somnath (Economic Journal, 1995)
A study was conducted to examine problems of implementing noneconomic conditionality, such as military expenditure reduction, in the granting of foreign aid in the presence of asymmetric information. Two conceptually separate principal-agent models are presented in order to capture the stylized facts of multilateral and bilateral aid negotiations: The first model is an application of the problem of adverse selection when there is more than one type of donor with varying objectives; the second extends moral hazard to double moral hazard, where neither the donor nor recipient can fully observe or verify each other's strategies. In multilateral aid negotiations, it is demonstrated that donors benefit from pooling their offers and that this does not make individual recipients worse off. In bilateral cases, it is revealed that double moral hazard introduces suboptimal levels of action and effort by donors and recipients and that donors can actually shift the burden of action to the latter group.